"Learn to fly": Identity and ideology in 21st century U.S. films on airplanes. - Goss, Brian Michael (Atlantic Journal of Communication)
This study analyzes ideology and identity in four post-September 11, 2001, U.S. films on flights. In particular, Flightplan and Red Eye celebrate the ordinary/extraordinary heroine in the context of the Bush administration's Global War on Terror (GWOT), as female heroines detect deviance while protecting the family and male authority. While playing on a misleadingly selective commitment to realism, United 93 orients to U.S. national identity in relation to other nations. Greengrass' film constructs identity in rightwing us/them terms compatible with GWOT and is nourished by a strong version of "Clash of Civilization" ideology. In the decade that followed, the redemption narrative of Non-stop shores up the male hero's authority. Once the villains' deviance is detected, the film rallies to the state security regime through Bill Marks' redemption while the film at once raises and understates the peril of violent domestic extremism in the United States. In each case, the films' devotion to mainstream ideology stages solutions to problems around identity that fail to grasp the extent of illiberal challenges and organic crisis within the United States.